Didactic Strategy for the Curricular Integration of the Library: Creation of Projects with Arduino and Scratch: Didactic Strategy for the Curricular Integration of the Library: Creation of Projects with Arduino and Scratch - Castro Araya, Hazel (2022)
The free software and hardware movement has socialized the technology allowing open access to it and thereby reducing the digital divide. In the classroom the opportunity has been found in these movements to boost classes and teaching and learning processes in general, however, the library has a preponderant role in such dynamization, because this space for the promotion of information can offer staff Teaching technology tools and knowledge of them for use through curriculum integration and pedagogical planning. This article shows the execution of a didactic strategy that teaches future professionals in library science to create projects for the curricular integration of their information units using Scratch software and Arduino microprocessors to support pedagogical planning. It also shows the projects that the students developed in said strategy and their opinion in the whole teaching and learning process experienced.